High toughness zirconia ceramic scribe and method of making the same

CN122940470APending Publication Date: 2026-10-20曾柱宁
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410351482.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-03-26
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0004]针对上述情况,为克服现有技术的缺陷,本发明提供了一种高韧性氧化锆陶瓷刻线刀及其制备方法,为了解决陶瓷刀具易出现刀面破损、崩刃的问题,本发明提出以片状Al2O3、Al2O3纳米颗粒、Si3N4颗粒、ZrO2颗粒为基体材料,与石墨烯包覆SiC颗粒结合,进行冻结、烧结制得陶瓷刀具基体,最后在基体表面进行加工处理,制得耐磨、高强度的陶瓷刻线刀

Benefits of technology

[0025]本发明提出以片状Al2O3、Al2O3纳米颗粒、Si3N4颗粒、ZrO2颗粒为基体材料,与石墨烯包覆SiC颗粒结合,进行冻结、烧结制得陶瓷刀具基体,最后在基体表面进行加工处理,制得耐磨、高强度的陶瓷刻线刀;石墨烯包覆SiC颗粒作为陶瓷刀具材料的增强相,采用激光液相辐照的方法处理碳化硅粉末,使其形成独特的石墨烯包覆SiC结构,能提高陶瓷刀具的耐磨性,又可以解决SiC和石墨烯在陶瓷基体中难分散的问题;通过冷冻铸造法以及热压烧结的方式将基体材料与石墨烯包覆SiC颗粒定向排列在一起得到致密结构的复合陶瓷材料,其中Al2O3和Si3N4之间会发生固溶反应,产生β-Sialon相和Sialon-X相,使复合陶瓷界面结合的更加紧密,纳米ZrO2颗粒作为层间相使复合陶瓷材料提供相变增韧作用;在对刀具基体表面进行加工处理时,在氮气、氢气和TiCl4氛围下进行等离子体气相沉积,在刀具表面形成氮化钛膜,进一步增强陶瓷刀具的抗弯强度、耐磨性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses a high-toughness zirconia ceramic scribing tool and its preparation method in the field of ceramic scribing tool manufacturing technology. The high-toughness zirconia ceramic scribing tool is obtained by processing the surface of a ceramic tool substrate. This invention uses sheet-like Al2O3, Al2O3 nanoparticles, Si3N4 particles, and ZrO2 particles as matrix materials, combined with graphene-coated SiC particles, and then freezes and sinterstensibly to obtain the ceramic tool substrate. Finally, the surface of the substrate is processed to obtain a wear-resistant, high-strength ceramic scribing tool.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of ceramic scribing tool preparation technology, specifically referring to a high-toughness zirconia ceramic scribing tool and its preparation method. Background Technology

[0002] A scribing tool is a carving tool used for scribing, sculpting, and cutting various materials. Common scribing tool materials include steel, high-speed steel, tungsten carbide, tungsten steel, and ceramics. Among them, ceramic materials have advantages in cutting fields due to their high hardness, high strength, high wear resistance, high heat resistance, and low affinity with metals. However, ceramic tool materials with a single matrix have relatively low strength, fracture toughness, thermal conductivity, and vibration resistance. During high-speed cutting, the chemical stability of the tool decreases, leading to easy wear on its surface, severe crater wear, and even chipping, which limits the widespread application of ceramic tools in the cutting field.

[0003] The existing technology currently has the following main problems: 1. Ceramic cutting tool materials have low friction reduction and wear resistance, and are prone to blade surface damage; 2. Ceramic cutting tools are brittle and have low fracture toughness, and are prone to chipping. Summary of the Invention

[0004] To address the above issues and overcome the shortcomings of existing technologies, this invention provides a high-toughness zirconia ceramic scribing tool and its preparation method. To solve the problem of surface damage and chipping in ceramic tools, this invention proposes using sheet-like Al2O3, Al2O3 nanoparticles, Si3N4 particles, and ZrO2 particles as matrix materials, combined with graphene-coated SiC particles, followed by freezing and sintering to obtain the ceramic tool matrix. Finally, the matrix surface is processed to obtain a wear-resistant, high-strength ceramic scribing tool.

[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows: The present invention proposes a high-toughness zirconia ceramic scribing tool, which is obtained by processing the surface of a ceramic tool substrate.

[0006] Preferably, the ceramic tool substrate is prepared by mixing raw materials with graphene-coated SiC particles, granulating the mixture, and then freezing and sintering it.

[0007] Preferably, the raw materials include sheet-like Al2O3, Al2O3 nanoparticles, Si3N4 particles, ZrO2 particles, and graphene-coated SiC particles.

[0008] Preferably, the processing involves plasma vapor deposition of the ceramic tool substrate in an atmosphere of nitrogen, hydrogen, and TiCl4.

[0009] This invention also provides a method for preparing a high-toughness zirconia ceramic scribing tool, specifically including the following steps:

[0010] (1) Take nano-SiC powder, disperse it in anhydrous ethanol to obtain a suspension, stir ultrasonically for 0.5-1h, irradiate with laser at 100r / min for 20-30min, centrifuge to take the precipitate, wash it and add a mixed acid solution of HF acid and dilute HCl until the pH value is 3-5, acid wash three times, rinse with anhydrous ethanol to obtain graphene-coated SiC particles.

[0011] (2) Al2O3 nanoparticles, Si3N4 particles, ZrO2 particles, graphene-coated SiC particles, sodium dodecyl sulfate, and polyvinylpyrrolidone were mixed and ball-milled in a ball mill for 6-9 hours with a ball-to-material ratio of 7-9:1. Flake Al2O3 was added and ball-milled for another 3 hours. 0.1-0.3 mL of isooctanol was added dropwise and mixed evenly to obtain a mixed sample. The sample was poured into a polytetrafluoroethylene mold and directionally frozen with liquid nitrogen at a cooling rate of 3 °C / min to obtain a frozen sample. The sample was then placed in a freeze dryer and freeze-dried at 10 Pa and 50 °C for 48 hours to obtain a layered porous ceramic preform.

[0012] (3) The layered porous ceramic preform prepared in step (2) is transferred to a vacuum atmosphere furnace and heated to 1000°C at a heating rate of 5°C / min under a vacuum of 20Pa. It is then heated to 1100°C under an Ar atmosphere and held for 4 hours for pre-sintering. After that, it is hot-pressed to obtain a dense composite ceramic knife matrix.

[0013] (4) The dense composite ceramic knife substrate prepared in step (3) is transferred to a medium-temperature vacuum atmosphere tube furnace, heated to 900-1050℃ in a hydrogen atmosphere of 3-5L / min, and held for 10min. In a mixed atmosphere of nitrogen and hydrogen, TiCl4 is introduced at a flow rate of 1.5L / min, and vapor deposition is carried out for 60-80min. The temperature is then reduced to room temperature to obtain a high-toughness zirconia ceramic scribing knife.

[0014] Preferably, in step (1), the amount of nano-SiC powder added to anhydrous ethanol is 1.5-2 g / L;

[0015] Preferably, in step (1), the energy density of the laser is 0.8 Jpulse. -1 cm -1 The laser frequency is 5Hz;

[0016] Preferably, in step (1), the volume ratio of the HF acid to the dilute HCl is 1:1;

[0017] Preferably, in step (2), the mass ratio of the Al2O3 nanoparticles, Si3N4 particles, ZrO2 particles, and graphene-coated SiC particles is 1:25-27:1:2-3.

[0018] In step (2), the amount of sodium dodecyl sulfate added is 0.1%-0.5% of the mass of Si3N4 particles;

[0019] In step (2), the amount of polyvinylpyrrolidone added is 1%-2% of the mass of Si3N4 particles;

[0020] In step (2), the mass ratio of the sheet-like Al2O3 to the Al2O3 nanoparticles is 2-3:1;

[0021] Preferably, in step (2), the ball mill rotation speed is 250-300 r / min;

[0022] Preferably, in step (3), the hot pressing sintering process is as follows: at 5 Pa, the temperature is increased to 1100°C at 20°C / min, and then increased to 1550°C at 10°C / min, and held for 1 hour.

[0023] Preferably, in step (4), the nitrogen flow rate is 5 L / min, and the nitrogen to hydrogen flow rate ratio is 0.5:1.

[0024] The beneficial effects achieved by this invention are as follows:

[0025] This invention proposes using sheet-like Al2O3, Al2O3 nanoparticles, Si3N4 particles, and ZrO2 particles as matrix materials, combined with graphene-coated SiC particles, and then freezing and sintering to obtain a ceramic tool matrix. Finally, the surface of the matrix is ​​processed to obtain a wear-resistant, high-strength ceramic engraving knife. Graphene-coated SiC particles serve as a reinforcing phase in the ceramic tool material. Silicon carbide powder is treated with laser liquid phase irradiation to form a unique graphene-coated SiC structure, which improves the wear resistance of the ceramic tool and solves the problem of difficult dispersion of SiC and graphene in the ceramic matrix. The process is achieved through freeze casting. The matrix material and graphene-coated SiC particles are oriented together by hot pressing sintering to obtain a dense composite ceramic material. In this process, a solid solution reaction occurs between Al2O3 and Si3N4 to produce β-Sialon and Sialon-X phases, making the composite ceramic interface more tightly bonded. Nano-ZrO2 particles act as interlayer phases to provide phase transformation toughening for the composite ceramic material. When processing the surface of the tool matrix, plasma vapor deposition is performed in a nitrogen, hydrogen and TiCl4 atmosphere to form a titanium nitride film on the tool surface, further enhancing the bending strength and wear resistance of the ceramic tool. Attached Figure Description

[0026] Figure 1 The figures show the wear rate test results of ceramic scribing tools prepared in the embodiments and comparative examples of the present invention;

[0027] Figure 2 The graph shows the bending strength test results of the ceramic scribing blades prepared according to the embodiments and comparative examples of the present invention;

[0028] Figure 3 The figure shows the fracture toughness test results of the ceramic scribing tool prepared in the embodiments and comparative examples of the present invention.

[0029] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used together with the embodiments of the invention to explain the invention and do not constitute a limitation thereof. Detailed Implementation

[0030] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those familiar to those skilled in the art. Furthermore, any methods and materials similar to or equivalent to those described herein may be applied to this invention. The preferred embodiments and materials described herein are for illustrative purposes only and do not limit the scope of this application.

[0032] Unless otherwise specified, the experimental methods used in the following examples are conventional methods; unless otherwise specified, the experimental materials and test strains used in the following examples were purchased from commercial channels.

[0033] Si3N4 particles (particle size 100nm, density 3.12g / cm³) 3 SiC powder was purchased from Shanghai Chaowei Co., Ltd.; Al2O3 flakes and Al2O3 nanoparticles (80nm particle size) were purchased from Beijing Wangyong Technology Co., Ltd.; ZrO2 particles (50-80nm particle size) were purchased from Xuancheng Jingrui New Materials Co., Ltd.; sodium dodecyl sulfate was purchased from Sinopharm Chemical Reagent Co., Ltd.; and polyvinylpyrrolidone was purchased from Tianjin Kemeier Chemical Reagent Co., Ltd.

[0034] Example 1

[0035] A high-toughness zirconia ceramic scribing tool is obtained by processing the surface of a ceramic tool substrate.

[0036] The ceramic tool substrate is prepared by mixing raw materials with graphene-coated SiC particles, granulating the mixture, and then sintering it.

[0037] The raw materials include sheet-like Al2O3, Al2O3 nanoparticles, Si3N4 particles, ZrO2 particles, and graphene-coated SiC particles.

[0038] The processing involves plasma vapor deposition on a ceramic tool substrate under nitrogen, hydrogen, and TiCl4 atmospheres.

[0039] This invention also provides a method for preparing a high-toughness zirconia ceramic scribing tool, specifically including the following steps:

[0040] (1) Take nano-SiC powder and disperse it in 100 mL of anhydrous ethanol at an addition rate of 1.5 g / L to obtain a suspension. Stir the suspension with ultrasonic stirring for 0.5 h and add it to a 0.8 J pulse under stirring at 100 r / min. -1 cm -1 Irradiate the sample with a laser with a laser frequency of 5 Hz for 20 min, centrifuge at 800 r / min for 3 min, take the precipitate, wash it with deionized water, add it to a mixed acid solution of HF acid and dilute HCl in a volume ratio of 1:1 until the pH value is 3, wash it three times with acid, and then rinse it with anhydrous ethanol to obtain graphene-coated SiC particles.

[0041] (2) Al2O3 nanoparticles, Si3N4 particles, ZrO2 particles, and graphene-coated SiC particles were mixed in a mass ratio of 1:25:1:2. Sodium dodecyl sulfate was added at 0.1% of the mass of Si3N4 particles, and polyvinylpyrrolidone was added at 1% of the mass of Si3N4 particles. After mixing evenly, the mixture was placed in a ball mill and ball-milled at 250 r / min for 6 h with a ball-to-material ratio of 7:1. At a mass ratio of 2:1 between sheet Al2O3 and Al2O3 nanoparticles, sheet Al2O3 was added and ball-milled for another 3 h. 0.1 mL of isooctanol was added dropwise and mixed evenly to obtain a mixed sample. The mixed sample was poured into a polytetrafluoroethylene mold and directionally frozen at a cooling rate of 3 °C / min to obtain a frozen sample. The frozen sample was then placed in a freeze dryer and freeze-dried at 10 Pa and 50 °C for 48 h to obtain a layered porous ceramic preform.

[0042] (3) The layered porous ceramic preform prepared in step (2) is transferred to a vacuum atmosphere furnace and heated to 1000°C at a heating rate of 5°C / min under a vacuum of 20Pa. Then it is heated to 1100°C under an Ar atmosphere and held for 4 hours for pre-sintering. Then it is hot-pressed for sintering. The hot-pressing sintering process is as follows: under 5Pa, the temperature is raised to 1200°C at 20°C / min, and then raised to 1550°C at 10°C / min and held for 1 hour to obtain a dense composite ceramic knife substrate.

[0043] (4) The dense composite ceramic knife substrate prepared in step (3) is transferred to a medium-temperature vacuum atmosphere tube furnace, heated to 1050℃ in a hydrogen atmosphere of 3L / min, and held for 10min. In a mixed gas atmosphere of 5L / min nitrogen flow rate and 1L / min hydrogen flow rate, TiCl4 flow rate of 1.5L / min is introduced, and vapor deposition is carried out for 60min. The temperature is then reduced to room temperature to obtain a high-toughness zirconia ceramic scribing knife.

[0044] Example 2

[0045] A high-toughness zirconia ceramic scribing tool is obtained by processing the surface of a ceramic tool substrate.

[0046] The ceramic tool substrate is prepared by mixing raw materials with graphene-coated SiC particles, granulating the mixture, and then sintering it.

[0047] The raw materials include sheet-like Al2O3, Al2O3 nanoparticles, Si3N4 particles, ZrO2 particles, and graphene-coated SiC particles.

[0048] The processing involves plasma vapor deposition of the ceramic tool substrate in an atmosphere of nitrogen, hydrogen, and TiCl4.

[0049] This invention also provides a method for preparing a high-toughness zirconia ceramic scribing tool, specifically including the following steps:

[0050] (1) Take nano-SiC powder and disperse it in 100 mL of anhydrous ethanol at an addition rate of 1.8 g / L to obtain a suspension. Stir the suspension with ultrasonic stirring for 0.5 h and add it to a 0.8 J pulse under stirring at 100 r / min. -1 cm -1 Irradiate the sample with a laser with a laser frequency of 5 Hz for 25 min, centrifuge at 800 r / min for 4 min, take the precipitate, wash it with deionized water, add it to a mixed acid solution of HF acid and dilute HCl in a volume ratio of 1:1 until the pH value is 4, wash it three times with acid, and then rinse it with anhydrous ethanol to obtain graphene-coated SiC particles.

[0051] (2) Al2O3 nanoparticles, Si3N4 particles, ZrO2 particles and graphene-coated SiC particles were mixed in a mass ratio of 1:26:1:3. Sodium dodecyl sulfate was added at 0.3% of the mass of Si3N4 particles and polyvinylpyrrolidone was added at 1.5% of the mass of Si3N4 particles. After mixing evenly, the mixture was placed in a ball mill and ball-milled at 300 r / min for 7 h with a ball-to-material ratio of 8:1. At a mass ratio of 3:1 between sheet Al2O3 and Al2O3 nanoparticles, sheet Al2O3 was added and ball-milled for another 3 h. 0.2 mL of isooctanol was added and the mixture was mixed evenly to obtain a mixed sample. The sample was poured into a polytetrafluoroethylene mold and directionally frozen at a cooling rate of 3 °C / min to obtain a frozen sample. The sample was then placed in a freeze dryer and freeze-dried at 10 Pa and 50 °C for 48 h to obtain a layered porous ceramic preform.

[0052] (3) The layered porous ceramic preform prepared in step (2) is transferred to a vacuum atmosphere furnace and heated to 1000°C at a heating rate of 5°C / min under a vacuum of 20Pa. Then it is heated to 1100°C under an Ar atmosphere and held for 4 hours for pre-sintering. Then it is hot-pressed for sintering. The hot-pressing sintering process is as follows: under 5Pa, the temperature is raised to 1100°C at 20°C / min, and then raised to 1550°C at 10°C / min and held for 1 hour to obtain a dense composite ceramic knife substrate.

[0053] (4) The dense composite ceramic knife substrate prepared in step (3) is transferred to a medium-temperature vacuum atmosphere tube furnace, heated to 1000℃ in a hydrogen atmosphere of 4L / min, and held for 10min. In a mixed gas atmosphere of 5L / min nitrogen flow rate and 1L / min hydrogen flow rate, TiCl4 flow rate of 1.5L / min is introduced, and vapor deposition is carried out for 70min. The temperature is then reduced to room temperature to obtain a high-toughness zirconia ceramic scribing knife.

[0054] Example 3

[0055] A high-toughness zirconia ceramic scribing tool is obtained by processing the surface of a ceramic tool substrate.

[0056] The ceramic tool substrate is prepared by mixing raw materials with graphene-coated SiC particles, granulating the mixture, and then sintering it.

[0057] The raw materials include sheet-like Al2O3, Al2O3 nanoparticles, Si3N4 particles, ZrO2 particles, and graphene-coated SiC particles.

[0058] The processing involves plasma vapor deposition of the ceramic tool substrate in an atmosphere of nitrogen, hydrogen, and TiCl4.

[0059] This invention also provides a method for preparing a high-toughness zirconia ceramic scribing tool, specifically including the following steps:

[0060] (1) Take nano-SiC powder and disperse it in 100 mL of anhydrous ethanol at an addition rate of 2 g / L to obtain a suspension. Stir the suspension with ultrasonication for 1 h and then add it to a 0.8 J pulse under stirring at 100 r / min. -1 cm -1 Irradiate the sample with a laser with a laser frequency of 5 Hz for 30 min, centrifuge at 800 r / min for 5 min, take the precipitate, wash it with deionized water, add it to a mixed acid solution of HF acid and dilute HCl in a volume ratio of 1:1 until the pH value is 5, wash it three times, and then rinse it with anhydrous ethanol to obtain graphene-coated SiC particles.

[0061] (2) Al2O3 nanoparticles, Si3N4 particles, ZrO2 particles, and graphene-coated SiC particles were mixed in a mass ratio of 1:27:1:3. Sodium dodecyl sulfate was added at 0.5% of the mass of Si3N4 particles, and polyvinylpyrrolidone was added at 2% of the mass of Si3N4 particles. After mixing evenly, the mixture was placed in a ball mill and ball-milled at 250 r / min for 6-9 h with a ball-to-material ratio of 9:1. At a mass ratio of 3:1 between flake Al2O3 and Al2O3 nanoparticles, flake Al2O3 was added and ball-milled for another 3 h. 0.3 mL of isooctanol was added and the mixture was mixed evenly to obtain a mixed sample. The sample was poured into a polytetrafluoroethylene mold and directionally frozen at a cooling rate of 3 °C / min to obtain a frozen sample. The sample was then placed in a freeze dryer and freeze-dried at 10 Pa and 50 °C for 48 h to obtain a layered porous ceramic preform.

[0062] (3) The layered porous ceramic preform prepared in step (2) is transferred to a vacuum atmosphere furnace and heated to 1000°C at a heating rate of 5°C / min under a vacuum of 20Pa. Then it is heated to 1100°C under an Ar atmosphere and held for 4 hours for pre-sintering. Then it is hot-pressed for sintering. The hot-pressing sintering process is as follows: under 5Pa, the temperature is raised to 1100°C at 20°C / min, and then raised to 1550°C at 10°C / min and held for 1 hour to obtain a dense composite ceramic knife substrate.

[0063] (4) The dense composite ceramic knife substrate prepared in step (3) is transferred to a medium-temperature vacuum atmosphere tube furnace, heated to 900°C in a hydrogen atmosphere of 5L / min, and held for 10min. In a mixed gas atmosphere of 5L / min nitrogen flow rate and 1L / min hydrogen flow rate, TiCl4 flow rate of 1.5L / min is introduced, and vapor deposition is carried out for 80min. The temperature is then reduced to room temperature to obtain a high-toughness zirconia ceramic scribing knife.

[0064] Comparative Example 1

[0065] This comparative example provides a high-toughness zirconia ceramic scribing tool and its preparation method. The only difference between this example and Example 1 is that nano-SiC powder is not added to any of the components, i.e., step (1) is not included. The remaining components and the component contents are the same as in Example 1.

[0066] Comparative Example 2

[0067] This comparative example provides a high-toughness zirconia ceramic scribing tool and its preparation method. The only difference between this and Example 1 is that SiC and graphene are directly added to all components without coating treatment. The remaining components and their contents are the same as in Example 1.

[0068] Comparative Example 3

[0069] This comparative example provides a high-toughness zirconia ceramic scribing tool and its preparation method. The only difference between this example and Example 1 is that the sample freezing treatment is not performed. The other components and component contents are the same as in Example 1.

[0070] Comparative Example 4

[0071] This comparative example provides a high-toughness zirconia ceramic scribing tool and its preparation method. The only difference between this example and Example 1 is that step (4) is not performed. The other components and component contents are the same as in Example 1.

[0072] Experimental Example

[0073] 1. Performance Testing

[0074] (1) Wear resistance: The ceramic scribing tools prepared in the examples and comparative examples were tested for wear rate under the same conditions using a reciprocating sliding friction and wear tester;

[0075] (2) Bending strength: The ceramic scribing blades prepared in the examples and comparative examples were tested for bending strength using a tensile testing machine with a three-point bending method. The span was 30 mm and the loading speed was 0.5 mm / min.

[0076] (3) Fracture toughness: The ceramic scribing blades prepared in the examples and comparative examples were used to measure the fracture toughness of the ceramic scribing blade material by indentation method. A diamond indenter was pressed on the sample surface and held for 15 seconds to make an indentation. Then, the diagonal of the indentation and the effective length of the crack were accurately measured by optical microscope.

[0077] Figure 1 The graph shows the bending strength test results of the ceramic scribing blades prepared according to the embodiments and comparative examples of the present invention; Figure 2 The figures show the wear rate test results of ceramic scribing tools prepared in the embodiments and comparative examples of the present invention; Figure 3 The figures shown are test results of the fracture toughness of the ceramic scribing tools prepared in the embodiments and comparative examples of the present invention; Figure 1The ceramic scribing tool prepared in the example has a bending strength, wear rate, and fracture toughness of 985 MPa, 11.25 × 10⁻⁶ MPa, and respectively. -8 mm 3 / N·m, 10.5MPa·m 1 / 2 The bending strength was increased by 33%, 28%, 19%, and 17% compared to the comparative examples; the wear rate was reduced by 45%, 43%, 54%, and 15% compared to the comparative examples; and the fracture toughness was increased by 54%, 48%, 33%, and 31% compared to the comparative examples, indicating that the ceramic scribing tool prepared in the embodiments of the present invention has better performance.

[0078] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

[0079] The present invention and its embodiments have been described above. This description is not restrictive, and the accompanying drawings are only one embodiment of the present invention. The actual application is not limited to this. In conclusion, if those skilled in the art are inspired by this description and design similar methods and embodiments without departing from the spirit of the present invention, they should all fall within the protection scope of the present invention.

Claims

1. A high-toughness zirconia ceramic scribing tool, characterized in that: The high-toughness zirconia ceramic scribing tool is prepared by processing the surface of a ceramic tool substrate. The ceramic tool substrate is prepared by mixing raw materials with graphene-coated SiC particles, granulating the mixture, and then freezing and sintering it. The raw materials include sheet-like Al2O3, Al2O3 nanoparticles, Si3N4 particles, ZrO2 particles, and graphene-coated SiC particles. The processing involves plasma vapor deposition of the ceramic tool substrate under nitrogen, hydrogen, and TiCl4 atmospheres.

2. The method for preparing a high-toughness zirconia ceramic scribing tool according to claim 1, characterized in that: Specifically, the steps include the following: (1) Take nano-SiC powder, disperse it in anhydrous ethanol to obtain a suspension, stir ultrasonically for 0.5-1h, irradiate with laser at 100r / min for 20-30min, centrifuge to take the precipitate, wash it and add a mixed acid solution of HF acid and dilute HCl until the pH value is 3-5, acid wash three times, rinse with anhydrous ethanol to obtain graphene-coated SiC particles. (2) Al2O3 nanoparticles, Si3N4 particles, ZrO2 particles, graphene-coated SiC particles, sodium dodecyl sulfate, and polyvinylpyrrolidone were mixed and ball-milled in a ball mill for 6-9 hours with a ball-to-material ratio of 7-9:

1. Flake Al2O3 was added and ball-milled for another 3 hours. 0.1-0.3 mL of isooctanol was added dropwise and mixed evenly to obtain a mixed sample. The sample was poured into a polytetrafluoroethylene mold and directionally frozen with liquid nitrogen at a cooling rate of 3 °C / min to obtain a frozen sample. The sample was then placed in a freeze dryer and freeze-dried at 10 Pa and 50 °C for 48 hours to obtain a layered porous ceramic preform. (3) The layered porous ceramic preform prepared in step (2) is transferred to a vacuum atmosphere furnace and heated to 1000°C at a heating rate of 5°C / min under a vacuum of 20Pa. It is then heated to 1100°C under an Ar atmosphere and held for 4 hours for pre-sintering. After that, it is hot-pressed to obtain a dense composite ceramic knife matrix. (4) The dense composite ceramic knife substrate prepared in step (3) is transferred to a medium-temperature vacuum atmosphere tube furnace, heated to 900-1050℃ in a hydrogen atmosphere of 3-5L / min, and held for 10min. In a mixed atmosphere of nitrogen and hydrogen, TiCl4 is introduced at a flow rate of 1.5L / min, and vapor deposition is carried out for 60-80min. The temperature is then reduced to room temperature to obtain a high-toughness zirconia ceramic scribing knife.

3. The method for preparing a high-toughness zirconia ceramic scribing tool according to claim 3, characterized in that: In step (1), the amount of nano-SiC powder added to anhydrous ethanol is 1.5-2 g / L; the energy density of the laser is 0.8 Jpulse. -1 cm -1 The laser frequency is 5 Hz; the volume ratio of the HF acid and dilute HCl is 1:

1.

4. The method for preparing a high-toughness zirconia ceramic scribing tool according to claim 4, characterized in that: In step (2), the mass ratio of the Al2O3 nanoparticles, Si3N4 particles, ZrO2 particles, and graphene-coated SiC particles is 1:25-27:1:2-3.

5. The method for preparing a high-toughness zirconia ceramic scribing tool according to claim 5, characterized in that: In step (2), the amount of sodium dodecyl sulfate added is 0.1%-0.5% of the mass of Si3N4 particles; the amount of polyvinylpyrrolidone added is 1%-2% of the mass of Si3N4 particles.

6. The method for preparing a high-toughness zirconia ceramic scribing tool according to claim 6, characterized in that: In step (2): the mass ratio of the sheet-like Al2O3 to the Al2O3 nanoparticles is 2-3:1; the ball milling speed is 250-300 r / min.

7. The method for preparing a high-toughness zirconia ceramic scribing tool according to claim 7, characterized in that: In step (3): the hot pressing sintering treatment method is to raise the temperature to 1100℃ at 20℃ / min under 5Pa, and then raise the temperature to 1550℃ at 10℃ / min and hold for 1h.

8. The method for preparing a high-toughness zirconia ceramic scribing tool according to claim 8, characterized in that: In step (4): the nitrogen flow rate is 5 L / min, and the flow rate ratio of nitrogen to hydrogen is 0.5:1.